A defined mix of cytokines mimics conditioned medium from cultures of bone marrow‐derived mesenchymal stem cells and elicits bone regeneration. (30th January 2017) - Katagiri, Wataru; Sakaguchi, Kohei; Kawai, Takamasa; Wakayama, Yukiko; Osugi, Masashi; Hibi, Hideharu
Abstract: Objectives: We previously reported that conditioned medium from cultures of bone marrow‐derived mesenchymal stem cells have strong potential to accelerate bone regeneration. We now examine in vitro and in vivo a defined cytokine cocktail that mimics the effects of conditioned medium on bone regeneration. Materials and methods: A cocktail of recombinant human insulin‐like growth factor‐1, vascular endothelial growth factor‐A and transforming growth factor‐β1 was prepared at concentrations similar to those in conditioned medium. Conversely, these cytokines were depleted from conditioned medium, and the effects of the cocktail, the conditioned medium and the cytokine‐depleted conditioned medium on bone regeneration were evaluated in vitro and in vivo. Results: The cytokine cocktail and conditioned medium enhanced cell migration, tube formation, and expression of osteogenic and angiogenic genes. Depletion of cytokines significantly decreased the effects of conditioned medium in vitro. Similarly, the cytokine cocktail and conditioned medium, but not cytokine‐depleted medium, increased bone regeneration in damaged rat calvarial bone. Immunohistochemistry indicated that the cytokine cocktail and conditioned medium strongly enhanced recruitment of endogenous stem cells and endothelial cells. Conclusions: The data indicate that the cytokine cocktail and conditioned medium enhance the migration of stem cells and endothelial cells to damaged bone, and elicit osteogenesis and angiogenesis.